Impact of maternal bifidobacteria and the mode of delivery on Bifidobacterium microbiota in infants - S. Sirilun (2018)
© 2015 Wageningen Academic Publishers. The aim of this study is to examine the influence of maternal intestinal and vaginal bifidobacteria on the colonisation of bifidobacteria in the gut of infants. Faecal samples from 120 healthy pregnant mothers within 1 month of delivery and from their infants at 1 month of age and 98 vaginal swabs from the mothers at the time of delivery were collected at a maternity hospital in Chiang Mai, Thailand. The faecal and vaginal samples were assayed by real-time PCR assays to detect Bifidobacterium species and to estimate the bifidobacterial copy numbers. After adjusting for the numbers of each Bifidobacterium species, delivery mode, and antibiotic use in infants by the age of 1 month, total counts of bifidobacteria in the mothers' faeces were associated with increased copy numbers of bifidobacteria in the faeces of breastfed infants. A caesarean section was also significantly associated with a decrease in the copy numbers of bifidobacteria in the faeces of infants. No significant correlation was found between the bifidobacterial copies of the vaginal swabs and those of the infants' faeces. The intes tinal bifidobacterial status of exclusively breastfed infants was significantly positive affected by vaginal delivery and high bifidobacterial copy numbers in their mothers' gut.